القوة الاقتصادية العظمى وعلاقتها بمنظمة التجارة العالمية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث دراسة لقضية تعتبر من أهم القضايا المعاصرة بالنسبة لجميع دول العالم, هذه القضية هي الهيمنة الأمريكية على منظمة التجارة العالمية كنتيجة للتحولات التي طرأت على النظام الدولي ما بعد انهيار المعسكر الاشتراكي، وظهور الولايات المتحدة الأمريكية كقوة عظمى تحتكر حكومتها أسباب التفوق, مسخرة تلك التحولات لتنصيب نفسها وصية على كل ما يجري في المعمورة, باستخدام هيمنتها على العديد من المنظمات الدولية, ويتناول البحث ذكر بعض الانتقادات الموجهة لعمل منظمة التجارة العالمية, وصولاً لتقديم بعض المقترحات التي من شأنها أن تسهم في تحقيق أهداف المنظمة. وبناء على ما تقدم تناول البحث أهم الأفكار التي تخدم الموضوع وفقاً لما يلي : 1-     النظام العالمي الجديد والتباس مفهوم الشرعية الدولية بالإضافة للمعالم السياسية لهذا النظام. 2-     مفهوم الشرعية الدولية وبعض الانتقادات الموجهة لعمل المنظمة. 3-     نتائج ومقترحات. This research studies an important modern issue which is the American hegemony on WTO due to the changes that happened in the international system after the collapse of the Socialistic Camp, the USA appeared as a great power that uses these changes to position itself as a trustee for what goes on in the world and it uses its hegemony on different international organizations. This research also studies the most important ways of the American hegemony with some criticism against WTO in order to offer suggestions to help to fulfill its aims. Thus, the research studies the most important ideas that serve the topic as follows: 1- New world order and suspect about international legality in addition to the political features of this order. 2- The international legality and some criticisms against the WTO job. 3- Results and suggestions.